A qualitative study on the health system-related needs in women survivors of rape - Leila Asadi; Mahnaz Noroozi; Hajar Salimi; Sara Jambarsang; Fardin Mardani (BMC, 2024)
Abstract Background Rape, as an adverse incidence, leads to irreparable complications and consequences in women. Provision of health services to women survivors of rape requires catering for their real needs and identifying current deficits as well as barriers. The present study aimed to explore health system-related needs in women survivors of rape. Methods In the present qualitative study, the participants consisted of 39 individuals, including 19 women survivors of rape and 20 individuals with work experience in providing services to women survivors of rape. The participants were selected using the purposive sampling method with a maximum variation in Isfahan, Iran. Data were collected through in-depth interviews as well as field notes and were concurrently analyzed via conventional qualitative content analysis method. Results After analyzing the interviews, the health system-related needs of women survivors of rape were classified into two main categories: 1- The need for efficient medical care services with three sub-categories, namely "receiving services with respect for privacy and confidentiality", "non-judgmental behavior and approach", and "the need to receive empathy and the feeling of not being alone", and 2- The need for desirable conditions and structure to provide services with two sub-categories, namely "the need to receive comprehensive and integrated services", and "establishing specialized centers for providing services to survivors". Conclusions Overall, explaining and highlighting the health system-related needs of women survivors of rape could provide a suitable basis for policy-making and planning according to their real needs. Receiving continuous services in separate centers with confidentiality and empathy could reduce the worries and concerns of women survivors of rape and help improve their health.